The multiple temporalities in testimony: the experienced past and its present legacies (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This paper deals with the multiple temporalities present in personal narratives, overlapping and interacting among themselves.Two types of research materials on memories of political violence and State repression are presented. First, life history data collected in the author’s previous research. Then, on the basis of data collected by other researchers, the analysis and reflection is focused on the historical con- ditions that allow for voice, listening –and also conditions for silence and concealment.This second theme is analyzed in the context of the possibilities of voice regarding armed struggle and sexual violence during the Argentine dictator- ship.
Keywords: Testimony; Temporalities; Memories